Correlation between Small Dense Low Density Lipoprotein Level with Major Adverse Cardiac Event in Acute Coronary Syndrome Patients - Maria Debby Maharatno; Hariadi Hariawan; Budi Yuli Setianto (ACI (Acta Cardiologia Indonesiana), 2016)
Background: Cardiovascular disease is one of major problems in developed and developing countries. Atherosclerosis process begins with endothelial dysfunction. Lipoprotein is important factor in atherogenesis. Previous study stated that about 50% of cardiovascular events happened in individuals with normal or low LDL, therefore LDL plasma level alone is not enough to identifyindividuals with major adverse cardiac events. Individuals with small dense LDL predominant have 3 times fold to have cardiovascular risk. The goal of this study is to know whether the level of sdLDL has impact on in hospital major adverse cardiac events (MACE) of acute coronary syndrome patients. Methods: This was a cross sectional study, enrolling patients with acute coronary syndrome admitted and hospitalized in ICCU of Dr.Sardjito Hospital since September of 2013 until June 2015. The small dense LDL (sdLDLD) level was measured with previous formula using routine blood lipid component. Major adverse cardiac events (MACE) were determined upon observation during horpitalisation and defi ned as death, reinfarction, cardiogenic shock, acute heart failure, ventricular tachycardia or ventricular fi brillation, prolonged angina pain, and the need for immediate coronary intervention. Results: There were 159 patients with mean age 60.80 ± 9.8 years involved in this study. Onehundred eighteen (118) or 73% of patients were male. The mean of sdLDL level in patients with MACE was 108.34 ± 37.94 g/dl and mean sdLDL level in patients without MACE was 105.54 ± 43.10 g/dl. The level of sdLDL in patients without MACE was lower than patients with MACE (p=0.705). In this study we found the cut- off sdLDL level is ≥ 108.085 for higher sdLDL level and < 108.085 for lower sdLDL level. The higher sdLDL level have the prevalence ratio of 1.25 to develop MACE, however the value was not statistically signifi cant.Conclusion: The sdLDL level did not correlate with MACE in hospitalised patients with acute coronary syndrome.Keywords: small dense LDL, acute coronary syndrome, MACE